A influência do processo decisório na cooperação governo-universidade-empresa: um estudo de caso sobre a organização universitária - Eberhart, Mara Elizete (2013)
The aim of this study was to analyze the implications of the decision-making process of a university in fulfilling its role in the triple-helix model having as the object of study the Universidade Tecnológica Federal do Paraná (UTFPR), Curitiba Campus. This research is categorized as qualitative and as a case study, of a descriptive nature, cross-sectional and ex-post facto. The methodological procedures that guided the data collection were: semi-structured interviews, documents and non-participant observation. The study included the time from 2007 to 2012. The interviews focused predefined categories in order to identify and analyze the characteristics of technology-transfer mechanisms adopted by the UTFPR, Curitiba Campus, and the implications of the decision-making process regarding the government-university-company cooperation. The analysis of the decision-making process was based on the settings of the university model projected by Hardy and Fachin (2000). Fourteen interviews with managers and teachers were conducted using the snowball method. Based on data analysis, it can be seen that the decision-making process in the UTFPR, Curitiba Campus, is consistent with the professional bureaucracy in which decisions are shaped by common interests, power is decentralized and shared, and professional authority is based on technical competence and not in the position that the person holds. The goal was towards professional development; the changes come from the standards of the job. The implications of the decision-making process in the university organization are related to the movement of the triple helix, which sometimes slows down or accelerates, occurring bilaterally and being impacted by three main elements: 1) the bureaucratic institution's own public procedures, which sometimes make the process time consuming; 2) the way service is provided when transfer of technology is requested by the productive sector: technological projects, individual consultancies, incubation and innovation centers, collaborative research, and research groups; 3) the existing barriers in relation to financial autonomy. It was also found that the innovation actions expanded, moving the focus from product innovation to innovation and organizational changes in which the University helps the company in some areas regarding the difficulties related to production and administration. It was highlighted in the transfer and innovation processes the multiple actions in the cooperation area, as Incubators, the Technology Hotel, the Green Office and the Post-graduate Programs. These projects are arising mainly from the time when the institution became a University, which happened in 2005. In this new context the participation of the UTFPR, Curitiba Campus, took place in the productive sector through its adaptability to the interests of the community, the globalization and the expected results of governmental policies and programs. Some elements stand out as the learning ability and organizational maintenance of the status quo for the recognition of its expertise by society and the bilateral movement, according to the triple helix, upon its acceleration, leading the institution to fulfill its role as a center of knowledge responsible for research that promotes the development of innovations affecting the knowledgeable society.